My Grandmother Drank the Qur'an: Liquid Readings and Permeable Bodies in Bosnia. Issue 1 (April 2021) - HadžiMuhamedović, Safet
Abstract : Starting with a curious childhood memory, the author considers the practices of imbibing – or otherwise transforming and internalising – sacred texts as modes of reading in their own right. At the heart of the argument is a call for a receptive apprehension of reading, open to worlds beyond substance dualism and the detachment of text and meaning residing therein. Kaleidoscopic autobiographical elements merge with and extend through a variety of transmutational, syncretic practices, such as the rituals of 'erasure' (e.g. kombe ) across the African continent, or the magical inscriptions ( zapisi ) and the ritual of 'horror pouring' ( salivanje strave ) in Bosnia. Water appears as a particularly efficacious agent, flowing between humans and more-than-humans and connecting different bodies, religions, and forms of knowledge. Noticing that the recurring motif of such practices is healing, the author wonders if the drinking of text might be a remedy against the political ontology of inter-corporeal distance. A radically intimate engagement with text, it is suggested, requires the kind of trust that allows for permeability – an always-potential openness, a new sort of liquid critical reading.